AN ANALYSIS OF STUDENTS’ VOCABULARY ABILITY THROUGH ANAGRAM IN SMK SANDHY PUTRA 2 MEDAN - yenita Sembiring (English Language Teaching Prima Journal (ELT), 2019)
AN ANALYSIS OF STUDENTS’ VOCABULARY ABILITY THROUGH ANAGRAM IN SMK SANDHY PUTRA 2 MEDAN Yenita Sembiring Faculty of Teaching Training and Education. University of Prima Indonesia yenitasembiring@unprimdn.ac.id This research is aimed to find the students’ vocabulary ability through Anagram. The research was conducted by using descriptive qualitative research design. The place of the research is SMK Sandhy Putra 2 Medan. The subject of the research were 29 students of the students in SMK Sandhy Putra 2 Medan. The instrument used in order to collect the data in this research is test. Test was given to the students in order to find the students’ vocabulary ability through Anagram. From the analysis of the data in the previous chapter, it was found that: There is one student got 72 ( 3,4%). There is one student who got 76 (3,4%), one students got 80 (3,4%), five students who got 84 (17,2%), twelve students who got 88 (41,3%), seven students who got 92 (24,1%), one students who got 96 (3,4%). From the data, the writer concluded that: (1) the students in SMK Sandhy Putra 2 has a good comprehension in vocabulary through anagram since their level of comprehension are good, very good and excellent. (2) From the findings above and from the observation done by the writer it can be concluded that students’ in SMK Sandhy Putra 2 Medan did not find any difficulties in vocabulary mastery through anagram.